Endoscopic enucleation vs endoscopic vaporization procedures for benign prostatic hyperplasia: how should we choose. Issue 46 (13th November 2020) - Yin, Xinbao; Chen, Jun; Sun, Hui; Liu, Ming; Wang, Zehua; Shi, Benkang; Zheng, Xueping
Abstract: Objective: To assess the safety and efficacy of different endoscopic procedures of the prostate techniques, by comparing endoscopic enucleation (EEP) and endoscopic vaporization procedures (EVP) of the prostate; and laser enucleation procedures (L-EEP) vs laser vaporization procedures (L-EVP) surgeries for benign prostatic hyperplasia. Methods: A systematic literature review was performed in December 2019 using PubMed, Embase and the Cochrane Library to identify relevant studies. Two analyses were carried out: (1) EEP vs EVP; and (2) L-EEP vs L-EVP. Efficacy and safety were evaluated using perioperative data, functional outcomes, including maximum urinary flow rate (Qmax), quality of life (QoL), international prostate symptom score (IPSS), postvoiding residual urine volume (PRV), and rate of complications. Meta-analyses were conducted using RevMan5.3. Results: Sixteen studies (4907 patients) evaluated EEP vs EVP, and 12 of them (4392 patients) evaluated L-EEP vs L-EVP. EEP showed improved functional outcomes compared with EVP. EEP was always presented a better Qmax at various follow-up times. EEP also associated with a reduced PRV and IPSS at 12 months postsurgery, an increased Qmax, and reduced IPSS and QoL score at both 24 and 36 months postsurgery. In addition, EEP was associated with less total energy utilized and retreatment for residual adenoma, but a longer catheterization time. Among other outcomes, there was no significant difference. L-EEP favors total energy used, retreatment for residual adenoma, and functional outcomes. L-EEP was associated with reduced PRV at 1, 6, and 12 months postsurgery, a greater Qmax at 6 and 12 months postsurgery, a lower IPSS at 12 months postsurgery, and higher Qmax and lower IPSS and QoL scores at 24 and 36 months postsurgery. However, there was no difference at 3 months postsurgery. No significant differences were observed for other perioperative data and complications. Conclusions: Both EEP and EVP displayed sufficient efficacy and safety for treating benign prostatic hyperplasia. EEP and L-EEP were favored in perioperative data, rate of complications, and functional outcomes. However, the clinical significance of those statistical differences was unclear. Hence, higher-quality randomized controlled trials may be needed to provide a clear algorithm. Abstract : Supplemental Digital Content is available in the text